Renewable electricity production in mountain regions: toward a people-centered energy transition agenda - Scott, Christopher A. (2023)
This paper examines progress and limitations in the transition from current dependence on carbon-based energy toward clean, renewable, and socially just energy in the Hindu Kush Himalaya and the Andes. Focusing on electricity production from sustainable hydropower, solar, and wind energy, the assessment does not cover biomass energy, although this is recognized to be an important energy source in these regions. Using meta-analysis methods, a set of 68 peer-reviewed publications was reviewed to systematically address 2 research questions: (1) Which electricity generation options in mountains can address local demands and adaptation needs while supporting broader decarbonization efforts? (2) What technical innovations, policy, and governance mechanisms can aid this transition? Considering governance, finance, individual and collective action, and science and technology dimensions of the transition challenge, recommendations for policymakers, mountain communities, and practitioners are made. These include setting up clear and effective policy measures, programs, and incentives to support energy transition plans and help mountain communities and energy practitioners to fully embrace the transition. Strong political commitment supported by international cooperation for a transition agenda centered on mountain people will enable community participation, stimulate technological innovation, and establish mechanisms to monitor and enforce social and environmental impact remediation. Este artículo examina los avances y las limitaciones en la transición de la actual dependencia de la energía basada en el carbono hacia una energía limpia, renovable y socialmente justa en el Hindu Kush Himalaya y los Andes. La evaluación, que se centra en la producción de electricidad a partir de energía hidroeléctrica, solar y eólica sostenibles, no cubre la energía de biomasa, aunque se reconoce que es una fuente de energía importante en estas regiones. Utilizando métodos de metanálisis, se revisó un conjunto de 68 publicaciones revisadas por pares para abordar sistemáticamente dos preguntas de investigación: (1) ¿Qué opciones de generación de electricidad en las montañas pueden abordar las demandas locales y las necesidades de adaptación al mismo tiempo que respaldan esfuerzos de descarbonización más amplios? (2) ¿Qué innovaciones técnicas, políticas y mecanismos de gobernanza pueden ayudar en esta transición? Teniendo en cuenta las dimensiones de gobernanza, finanzas, acción individual y colectiva y ciencia y tecnología del desafío de la transición, se formulan recomendaciones para los formuladores de políticas, las comunidades de montaña y los profesionales. Estos incluyen el establecimiento de medidas políticas, programas e incentivos claros y eficaces para apoyar los planes de transición energética y ayudar a las comunidades de montaña y a los profesionales de la energía a abrazar plenamente la transición. Un fuerte compromiso político respaldado por la cooperación internacional para una agenda de transición centrada en los pueblos de las montañas permitirá la participación comunitaria, estimulará la innovación tecnológica y establecerá mecanismos para monitorear y hacer cumplir la remediación del impacto social y ambiental.